Zinc Oxide Nanoparticle Photodetector. (28th May 2012) - Chang, Sheng-Po; Chen, Kuan-Jen
Abstract : A zinc oxide (ZnO) nanoparticle photodetector was fabricated using a simple method. Under a 5 V applied bias, its dark current and photocurrent were1.98 × 10 - 8 and9.42 × 10 - 7  A, respectively. In other words, a photocurrent-to-dark-current contrast ratio of 48 was obtained. Under incident light at a wavelength of 375 nm and a 5 V applied bias, the detector's measured responsivity was 3.75 A/W. The transient time constants measured during the turn-ON and turn-OFF states wereτ ON = 204  s andτ OFF = 486  s, respectively.